Audit committee characteristics and corporate governance disclosure: evidence from Vietnam listed companies - Hong Hanh Ha (Cogent Business & Management, 2022)
The study examines the association between audit committee characteristics, namely audit committee independence, audit committee financial expertise, audit committee gender diversity, size of audit committee and frequency of audit committee meeting, and corporate governance disclosure (CGD). The paper develops a comprehensive literature review using a bibliometric analysis with Scopus database from 2004 to 2022 and offers insight into the relationship between audit committee attributes as independent variables and level of corporate governance disclosure as a dependent variable. The dependent variable is measured basing on a scorecard of Vietnam-Listed Company Awards (VLCA). The set of scorecard questionnaire is then Cronbach Alpha tested to assure the reliability and consistency. The result contributes to extant literature a measurement of CGD in Vietnam. The multiple regression is applied over a sample of 210 non-financial listed companies in 2021. The findings show that audit committee independence and size of audit committee are significantly associated with level of CGD. The empirical evidence also reveals that firm size is statistically linked to CGD indicating the capital demand of large companies. Overall, the study might be of interest to professionals, policymakers and regulators regarding the establishment of regulations concerning the audit committee structure.
Keywords: 650; Audit committee; Vietnam; audit committee characteristics; corporate governance disclosure; corporate governance reports